1995
DOI: 10.1007/s001250050326
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering therapy may retard the progression of diabetic nephropathy

Abstract: SummaryThere is experimental evidence to suggest that hypercholesterolaemia may play a pathogenetic role in progressive glomerular injury. We investigated the effect of cholesterol-lowering therapy on the progression of diabetic nephropathy in 34 patients with non-insulin-dependent diabetes mellitus. Patients were randomly assigned in a single-blind fashion to treatment with either lovastatin, an HMG CoA reductase inhibitor (n = 16; mean dose 30.0 + 12.6 mg/day) or placebo (n = 18) for 2 years. Renal function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Twenty-nine trials with 4,968 participants reported data regarding the effects of statins on changes in proteinuria or albuminuria. Of these, 11 studies with a total of 2,833 participants provided data for urinary protein excretion 12,38,[46][47][48][49]51,58,62,67,73 ; 12 studies with 1,227 participants, urinary albumin excretion [43][44][45]52,54,55,63,[77][78][79][80][81] ; 5 studies with 788 participants, ACR 60,71,76,82 ; and 1 study with 120 participants, PCR. 69 The standardized mean difference in change in proteinuria or albuminuria was statistically significant at 20.65 (95% CI, 20.94 to 20.37) compared with the placebo or usual-care control groups, with substantial .…”
Section: Effect On Proteinuria and Albuminuriamentioning
confidence: 99%
“…Twenty-nine trials with 4,968 participants reported data regarding the effects of statins on changes in proteinuria or albuminuria. Of these, 11 studies with a total of 2,833 participants provided data for urinary protein excretion 12,38,[46][47][48][49]51,58,62,67,73 ; 12 studies with 1,227 participants, urinary albumin excretion [43][44][45]52,54,55,63,[77][78][79][80][81] ; 5 studies with 788 participants, ACR 60,71,76,82 ; and 1 study with 120 participants, PCR. 69 The standardized mean difference in change in proteinuria or albuminuria was statistically significant at 20.65 (95% CI, 20.94 to 20.37) compared with the placebo or usual-care control groups, with substantial .…”
Section: Effect On Proteinuria and Albuminuriamentioning
confidence: 99%